Infectious diseases : a geographic guide - Petersen, Eskild; Chen, Lin H.; Schlagenhauf-Lawlor, Patricia (John Wiley & Sons Inc., 2017)
The second edition of this concise and practical guide describes infections in geographical areas and provides information on disease risk, concomitant infections (such as co-prevalence of HIV and tuberculosis) and emerging bacterial, viral and parasitic infections in a given geographical area of the world.- Resumé vydavatel
Keywords: infekční nemoci; epidemie; epidemiologie -- metodologie; lékařská geografie; topografie; infectious diseases; epidemics; epidemiology -- methodology; medical geography; topography; elektronické knihy; sborníky; electronic books; papers of several authors